The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the 5th International Conference on Computational Methods in Structural Dynamics and Earthquake Engineering (COM 2015
DOI: 10.7712/120115.3455.810
|View full text |Cite
|
Sign up to set email alerts
|

Multigrid Solver With Domain Decomposition Smoothing for Steady-State Incompressible Fsi Problems

Abstract: Abstract. In this paper we investigate the numerical performance of a monolithic Newtonmultigrid solver with domain decomposition smoothers for the solution of a class of stationary incompressible FSI problems. The physics of the problem is described using a monolithic approach, where mass continuity and stress balance are automatically satisfied across the fluidsolid interface. The deformation of the fluid domain is taken into account within the nonlinear Newton iterations according to an Arbitrary Lagrangian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 18 publications
0
6
0
2
Order By: Relevance
“…All these tests were validated with respect to the available literature results. We refer to [2] for the validation of FSI1-S-2D. In the time-dependent simulations both profiles are multiplied by α(t) given by…”
Section: Richardson-schwarz Smoothermentioning
confidence: 99%
See 1 more Smart Citation
“…All these tests were validated with respect to the available literature results. We refer to [2] for the validation of FSI1-S-2D. In the time-dependent simulations both profiles are multiplied by α(t) given by…”
Section: Richardson-schwarz Smoothermentioning
confidence: 99%
“…We leave the testing and profiling of the parallel version of our solver to a future work. average cond 1 9.21 · 10 5 3.70 · 10 6 1.60 · 10 7 5.99 · 10 7 2.42 · 10 8 max cond 1 1.55 · 10 6 6.66 · 10 6 2.68 · 10 7 1.06 · 10 8 4.23 · 10 8 average cond 2 2.99 · 10 5 1.52 · 10 6 1.54 · 10 7 9.02 · 10 8 6.69 · 10 9 max cond 2 3.03 · 10 5 6.22 · 10 6 8.64 · 10 7 5.36 · 10 9 3.82 · 10 10…”
Section: Richardson-schwarz Smootherunclassified
“…Recent works showed that the above equation ordering is ill‐conditioned for steady‐state problems, and it becomes unstable for time‐dependent problems as the time step increases. Such a behavior can be easily explained by looking at the diagonal terms Kmonospaceds and Smonospaceus in the first and third rows of (26).…”
Section: Preconditionersmentioning
confidence: 99%
“…For steady state problems, such terms are identically zero, and for time dependent problems they become quite small for large time steps, resulting in a Jacobian matrix with zero or small diagonal terms. In Aulisa et al, a stable row/column pivoting alternative has been proposed,
…”
Section: Preconditionersmentioning
confidence: 99%
See 1 more Smart Citation